Rate of pancreatic fistula laparoscopic versus open Whipple Comparative study-1 - Fazl e Akbar; Muhammad Nadeem; Shah Abbas; Muslihuddin; Inayatullah Khan; Farooq Khan; Waqas Ahmad; Bashirullah (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
This study was carried out to explore the Rate of pancreatic fistula laparoscopic versus open Whipple. Materials and Methods: A retrospective study was carried out on 70 patients who had pancreaticoduodenectomy at Saidu Teaching Hospital, Swat - Pakistan between July 2020 and June 2021 after taking approval from the ethical committee of the institute. All individuals’ demographic and perioperative information was gathered, including information on their preoperative health, the need for surgery, their history of jaundice and the nature of the procedure. SAS statistical Software (version 9.1) was used for analysis. Results: A total of 70 patients who had done pancreaticoduodenectomy. The patients were divided into two groups. Laparoscopic pancreaticoduodenectomy (LP) N=35 and open pancreaticoduodenectomy (OP) N=35.Out of them male were n=40 (57.1%) and female were n=30(42.85). Between the two groups there was no statistical deference in ASA class, BMI, sex, age and abdominal surgery. In both groups pancreatic fistula were observed. LP group had grade A n=2(5.7%) pancreatic fistula (PF) While the frequency of grade B and C PF was absent in LP group. The prevalence of (PF) was maximum in the OP group. Over all 11.4% of patients had PF. Out of which 50% had Grade A, 25% had Grade B and 25% C pancreatic fistula Conclusion; the rate of pancreatic fistula is more prevalent in OP as compare to LP. So LP is better option as compared to OP for the pancreaticoduodenectomy.